Developing of novel therapeutics for breast cancer: targeting the Notch ligand DLL1 - Sales Dias, Joana (2021)
"Breast cancer (BC) is the second main cause of cancer related deaths for women worldwide. Despite significant advances in BC treatment, it remains a considerable clinical challenge and there is an unmet need to design new and more effective drugs to treat this disease. The Notch signaling pathway is an evolutionary conserved cell-to-cell communication system involved in a multitude of cellular processes, such as stem cell self-renewal, cellular homeostasis, proliferation, migration and apoptosis, playing an important role in normal breast biology.(...)"